PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI - Wiswari, Ni Kadek Ayu; Sudibya, I Gede Adnyana (E-Jurnal Manajemen; Vol 5 No 12 (2016), 2016)
The purpose of this study was to determine the effect of transformational leadership and organizational commitment on job satisfaction and employee performance. To achieve these objectives done gathering data by means of questionnaires and interviews. Questionnaires were administered to respondents (employees), to further analyzed using path analysis (path analysis). The employee population as many as 74 employees. With the population of more than 74 employees will use the entire population as the sample (sample saturated). Based on the analysis that the obtained results transformational leadership influence on employee job satisfaction. Organizational commitment influence on employee satisfaction. Job satisfaction influence on employee performance. Transformational leadership influence on employee performance. Organizational commitment influence on employee performance. For further research is expected to add another variable that is thought to affect satisfaction and employee performance so that the scope of the research results could be wider.
Keywords: transformational leadership, commitment, satisfaction, performance